2020
DOI: 10.1103/physrevb.102.214412
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling local heat contributions in interacting magnetic nanoparticles

Abstract: Recent experiments on magnetic nanoparticle hyperthermia show that the heat dissipated by particles must be considered locally, instead of characterizing it as a global quantity. Here we show theoretically that the complex energy transfer between nanoparticles interacting via magnetic dipolar fields can lead to negative local hysteresis loops and does not allow the use of these local hysteresis loops as a temperature measure. Our model shows that interacting nanoparticles release heat not only when the nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…Another key aspect defining the heating performance is the particle assembling, as it is often observed that particles tend to aggregate after cell internalisation, 41 which may completely define their heat release in comparison with the randomly dispersed case. [42][43][44][45] The assembling process is defined by a complex interplay between a broad range of parameters, including the media properties (viscosity, pH), the nanoparticle characteristics (size, shape, anisotropy), the field parameters (frequency and amplitude) and, obviously, the sample concentration see e.g. Bakuzis et al and references therein.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another key aspect defining the heating performance is the particle assembling, as it is often observed that particles tend to aggregate after cell internalisation, 41 which may completely define their heat release in comparison with the randomly dispersed case. [42][43][44][45] The assembling process is defined by a complex interplay between a broad range of parameters, including the media properties (viscosity, pH), the nanoparticle characteristics (size, shape, anisotropy), the field parameters (frequency and amplitude) and, obviously, the sample concentration see e.g. Bakuzis et al and references therein.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This has implications on magnetic hyperthermia. The area enclosed by global hysteresis loops-but not local ones [45]-is correlated with the amount of heat that can be generated. One sees that this heat can be increased or decreased by large amounts when ligand friction/stickiness is increased, depending on whether particle agglomerates have sufficient time to follow the oscillating applied field.…”
Section: Hysteresis Loopsmentioning
confidence: 99%
“…The practical applications of MH therapy require accurate predictions of intensity of the heat generation and temperature of the heated region. There are many factors which influence the heating efficiency, including frequency and amplitude of the field, shape, size, concentration and magnetic properties of the particles (see [8][9][10]).…”
Section: Introductionmentioning
confidence: 99%